Integrating Graduate Attributes with Assessment Criteria in Business Education: Using an Online Assessment System - Thompson, D.; Treleaven, L.; Kamvounias, P.; Beem, B.; Hill, E. (Journal of University Teaching and Learning Practice, 2008)
This paper describes a study of the integration of graduate attributes into Business education using an online system to facilitate the process. ‘ReView’ is a system that provides students with criteria-based tutor feedback on assessment tasks and also provides opportunities for online student self-assessment. Setup incorporates a process of ‘review’ whereby assessment criteria are grouped into graduate attribute categories and reworded to make explicit the qualities, knowledge and skills that are valued in student performance. Through this process, academics clarify and make explicit the alignment of assessment tasks to learning objectives and graduate attribute development across units and levels of a program of study. Its application in three undergraduate Business units was undertaken as a collaborative action research project to improve alignment of graduate attributes with assessment, identification of assessment criteria and feedback to students. This paper describes the use of Review and presents an analysis of post-ReView data that has institutional implications for improving assessment and self-assessment practices.